Pregnancy planning does not interfere with child development in children aged from 11 to 23 months old - Katherine Solís-Cordero; Luciana Assis Couto; Luciane Simões Duarte; Ana Luiza Vilela Borges; Elizabeth Fujimori
Objective: to analyze the correlation between child development and pregnancy planning and other associated aspects. Method: a cross-sectional study conducted with 125 mother-child dyads, the children aged from 11 to 23 months old and attending daycare centers located in socially disadvantaged areas. Child development according to domains was assessed using the Ages & Stages Questionnaire-BR and pregnancy planning was evaluated through the London Measure of Unplanned Pregnancy. The mothers were interviewed at their homes and non-parametric tests were used for data analysis. Results: 17.6% of the pregnancies were unplanned, 24.8% were planned and 57.6% were ambivalent. Inadequate development in the different domains ranged from 21% to 40% and was not associated with pregnancy planning. However, the "communication" domain was associated with Bolsa Família and the "personal/social" and "communication" domains, with gender; while "personal/social", "broad motor coordination" and "fine motor coordination" were domains related to the child's age. Conclusion: no correlation between pregnancy planning and child development was observed; however, the low frequency of planned pregnancies and the high percentages of inadequate child development show the need to invest in the training of health professionals, both for contraceptive care and preconception health and for the promotion of child development, especially in socioeconomically disadvantaged contexts.